2022
DOI: 10.1109/jestpe.2021.3094278
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Electromagnetic Transient (EMT) Equivalent Model of Solid-State Transformer

Abstract: Accurate and efficient electromagnetic transient (EMT) simulation of various types of solid-state transformers (SST) is extremely time-consuming due to the complex module structure, flexible topology connections, large number of electrical nodes and simulation time-steps limited in the range of micro-seconds. Therefore, it is urgent to develop the EMT equivalent modelling and fast simulation of SSTs for system level studies. Taking the modular multilevel converter (MMC) based SST as an example, this paper prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Gao et al scholars proposed a modular structure that can accelerate. The results showed that the acceleration model carried a larger order of magnitude while ensuring accuracy [7]. Ying et al scholars proposed an electronic transformer based on coupling capacitors, and designed a self-maintaining duty cycle circuit to achieve load and power regulation.…”
Section: Related Workmentioning
confidence: 99%
“…Gao et al scholars proposed a modular structure that can accelerate. The results showed that the acceleration model carried a larger order of magnitude while ensuring accuracy [7]. Ying et al scholars proposed an electronic transformer based on coupling capacitors, and designed a self-maintaining duty cycle circuit to achieve load and power regulation.…”
Section: Related Workmentioning
confidence: 99%
“…It is a viable option because it combines high flexibility with energy flow, provides network infrastructure, and connects DC networks to Media-Voltage (MV) and Low-Voltage (LV) networks (LV). [5]- [6]. Although additional power functions are required, the solid-state transformer (SST), primarily composed of power electronics and a highfrequency magnetic link (HFML), represents significant potential for resolving current energy-quality issues.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the circuit analysis is changed to a matrix solution, and the modeling method becomes applicable for arbitrary multi-port PMs. Relying on the research of [3], [14], and [15], the method in [14] is now applicable to various kinds of multiport PM topologies and can be used for PETs and other PE equipment.…”
mentioning
confidence: 99%